Internet Survey of Participant Demographics and Risk Factors for Injury in Flyball Dogs - Montalbano, Christina; Gamble, Lauri-Jo; Walden, Katherine; Rouse, Jennifer; Mann, Sabine; Sack, Danny; Wakshlag, Lauren G.; Shmalberg, Justin W.; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2019)
Background: Injury risk in canine sprinting sports, such as greyhound racing and agility, have been previously documented through various surveys. Flyball, another sprinting canine sport with similar athletic requirements to agility, has yet to be assessed for factors associated with injury. The aim of this study was to determine injury prevalence and assess for risk factors for injury in flyball dogs. Methods: Survey data from 375 flyball participants was collected and analyzed. Data collected included patient-specific variables, equipment use, training/competition practices, and injury occurrence and localization. Univariate analysis was utilized for all variables of interest, followed by backwards nominal logistic regression to identify variables associated with increased risk of injury, with a p < 0.05 defined as significant. Results: Thirty-nine percent of dogs incurred at least one injury with 172 injuries reported. Injuries to the limbs were common (30.8% affecting forelimbs, 25.6% affecting hindlimbs), with the paw or nail the most frequently reported injured area (19.2%). Only protective wrap use and age were significantly associated with injury in the final nominal regression model (p < 0.01). A biphasic injury rate with more injuries in younger dogs was observed, and injuries peaked by 6 years of age. Use of carpal wraps was positively associated with increased injury risk. Conclusions: These findings suggest an association between younger dogs and greater risk of injury, as well as identify a need to further investigate the utilization of wraps and potential association between injury risk among flyball participants.